Explicit solutions of generalized nonlinear Boussinesq equations - Doğan Kaya (Journal of Applied Mathematics)
By considering the Adomian decomposition scheme, we solve a generalized Boussinesq equation. The method does not need linearization or weak nonlinearly assumptions. By using this scheme, the solutions are calculated in the form of a convergent power series with easily computable components. The decomposition series analytic solution of the problem is quickly obtained by observing the existence of the self-canceling “noise” terms where sum of components vanishes in the limit.